The Influence Of Work Environment, Work Motivation, And Company Performance On Employee Satisfaction At PT Bakrie Sumatera Plantations Kisaran - Vina Dwi Winata; Em Yusuf Iis; Yanita Yanita; Khairawati Khairawati (PT. Intelek Cendikiawan Nusantara, 2025)
Please This study aims to analyze the influence of work environment, work motivation, and company performance on employee satisfaction at PT Bakrie Sumatera Plantations Kisaran. The research uses a quantitative descriptive approach with a saturated sampling technique involving 122 permanent employees as respondents. Data were collected through questionnaires distributed via Google Forms and analyzed using multiple linear regression with the SPSS 25 program. The results indicate that the work environment, work motivation, and company performance have a positive and significant effect on employee satisfaction both partially and simultaneously. Among the three independent variables, company performance has the greatest impact on employee satisfaction, followed by work motivation and the work environment. These findings suggest that a comfortable work environment, strong employee motivation, and high company performance contribute significantly to increasing employee satisfaction levels. Therefore, management is encouraged to create a conducive work environment, enhance motivational strategies, and improve overall company performance to maintain employee loyalty and productivity.